MODEL TRANSFORMASI KETERAMPILAN PAWANG JALUR DI KABUPATEN KUANTAN SINGINGI - Yusra, Halqi Yusra Halqi; Natuna, Daeng Ayub Natuna Ayub; Irja, Desti Irja Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Model transformation handler skills in the path of this research is the removal of the activity or function handler berupakan skills to others or prospective handler, starting from the preparation to create a path to the return path or the path to the house unseen. The main focus of this study was to determine the activity or function and the model transformation handler skills in Kuantan Singingi track. On the basis of this primary focus, then there are 23 sub focus the concentration. The method used is descriptive qualitative. The place of this research will be carried on in Kuantan Singingi, where tradition or culture flourish and be preserved spur lines. Data were collected through interviews and documentation to the informant. Analysis of data using Interpretative Approach, in which this approach social and human activity is treated as text. Results of the study were 23 activities or activities related to the spur track handler and 23 are also role or function handler track on each activity and the activity. The skills acquired by the teacher or by a handler from the handler to the teacher candidates through a process of transformation skills. The process of transformation of the line handler skills through direct guidance and direct learning, task or assignment, by way of training, and practice.keywords: transformation, the skills, the handler, and path